Analisis Kesalahan dalam Menyelesaikan Soal Bangun Ruang Sisi Datar Berdasarkan Teori Nolting Ditinjau dari Gaya Kognitif Siswa Kelas IX MTS Muhammadiyah Surakarta - Reza Mozan Ariazena; Ira Kurniawati; Yemi Kuswardi (Jurnal Karya Pendidikan Matematika, 2025)
This study aims to describe and analyse the types of errors made by student of IX MTs Muhammadiyah Surakarta in solving problems on the polyhedron material based on Nolting’s theory. This research uses indicator of the types of Nolting errors, namely Misread direction Errors, Careless Errors, Concept Errors, Application Errors, and Test-taking Errors. This study uses a qualitative approach with a descriptive method. The sampling technique used was purposive sampling, with four research subjects in grade IX B MTs Muhammadiyah Surakarta for the 2024/2025 academic year who had been classified based on their cognitive styles using with the Group Embedded Figures Test (GEFT) instrument. The data collection technique was a tes techniques and interview. The data collection techniques used were test and interview techniques. The validity was tested using the triangulation method, while the data analysis technique was carried out through the stages of data reduction, data presentation, and conclusion drawn. The analysis revealed that students with a field dependent cognitive style committed all types of errors outlined by Nolting, while those with a field independent style were more prone to Misread Direction Errors, Careless Errors, and Test-taking Errors. Among all errors types, Test-taking Errors were the most commonly observed.